PENGAMBILAN KEPUTUSAN PADA PENGAJUAN SISWA-SISWI KE BEASISWA PIP MENGGUNAKAN METODE AHP DAN TOPSIS - Halim, Muhammad Yusuf; Firdaus, Muhammad Bambang (J-Icon : Jurnal Komputer dan Informatika, 2025)
Education is an effort to help individuals achieve their maximum potential. In accordance with Law Number 20 of 2003 concerning the National Education System, basic education is the earliest level in the national education system. State Elementary School (SD) 018 Loa Janan is an elementary school located in Tani Bahagia Hamlet, Batuah Village, Loa Janan District, Kutai Kartanegara Regency, East Kalimantan Province. To support the welfare of its students, the school enrolls its students in various scholarship programs, including the Smart Indonesia Program (PIP). However, the absence of clear criteria causes difficulties for schools in determining which students are eligible to apply for PIP scholarships. Therefore, a Decision Support System (SPK) will be implemented to assist schools in the selection process of students who will be proposed for PIP scholarships. This research aims to achieve this. Decisions will be taken using a combination of the Analytical Hierarchy Process (AHP) method to calculate criteria weights and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method to rank alternatives. There are five criteria and 67 alternatives. Criteria weights will be calculated using the AHP method, while alternative ranking will be carried out using the TOPSIS method. The calculation results show that a student named Elbara Mukti received first place with a preference value of 0.8589. Students with the highest preference scores will be proposed by the school to receive a PIP scholarship